A critical perspective on corporate social responsibility: Towards a global governance framework - Bobby Banerjee, Subhabrata (Critical perspectives on international business, 2014)
Purpose - The purpose of this paper is to argue that there are structural and functional limits to corporate social responsibility (CSR) that determine the boundary conditions of corporate social initiatives. The current preoccupation with win-win situations in CSR may not serve societal interests. For CSR to produce social outcomes that are not necessarily constrained by corporate rationality there needs to be a change in the normative framework of public decision making at the institutional level. The author develops a global governance framework for CSR that provides more democratic forms of decision making in the political economy that will enable corporate social responsibility to overcome the constraints imposed by corporate rationality. Design/methodology/approach - This is a conceptual paper and critique. Findings - The author develops a global governance framework for CSR that provides more democratic forms of decision making in the political economy that will enable corporate social responsibility to overcome the constraints imposed by corporate rationality. Originality/value - The paper contributes to theoretical development of CSR.